2013
DOI: 10.1111/1755-5922.12029
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry Leaf Diet Protects Against Progression of Experimental Autoimmune Myocarditis to Dilated Cardiomyopathy Via Modulation of Oxidative Stress and MAPK‐Mediated Apoptosis

Abstract: SUMMARYAim of the study: To examine the protective effects of dietary administration of Mulberry leaves (ML) on postmyocarditis dilated cardiomyopathy (DCM) focusing on oxidative and endoplasmic reticulum stresses and adverse myocardial remodeling. Materials and methods: In this study, we used a rat model of cardiac myosin-induced experimental autoimmune myocarditis to test the effects of ML diet (MLD) (5%) on various markers of cardiac remodeling and function. After 4 weeks of immunization, the rats were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…The remaining excised kidneys were cut into 2 mm thick transverse slices and fixed in 10% formalin. Sections of 3-5 μm thickness were stained with hematoxylin and eosin (H&E) or Masson trichrome for histological examination [15]. A histomorphological evaluation of all the renal sections was carried out in a blinded fashion.…”
Section: Histopathological Studiesmentioning
confidence: 99%
“…The remaining excised kidneys were cut into 2 mm thick transverse slices and fixed in 10% formalin. Sections of 3-5 μm thickness were stained with hematoxylin and eosin (H&E) or Masson trichrome for histological examination [15]. A histomorphological evaluation of all the renal sections was carried out in a blinded fashion.…”
Section: Histopathological Studiesmentioning
confidence: 99%
“…Moreover, approximately 20%‐50% of affected patients have a family history, suggesting that heredity is an important cause of this disease . Of crucial importance, increased oxidative stress has been implicated in the adverse cardiac remodelling associated with DCM, which may trigger myocardial inflammation, cardiomyocyte dysfunction and apoptosis . Similarly, it is suggested that in the development of DCM, oxidative stress promotes cellular senescence and death, and is concomitantly associated with the decreased cardiac function .…”
Section: Introductionmentioning
confidence: 99%
“…10 Besides, a mulberry leaf diet was also reported to protect against the progression of experimental autoimmune myocarditis to dilated cardiomyopathy via modulation of oxidative stress and MAPK-mediated apoptosis. 11 However, the functional components that inhibited apoptosis in the above studies were not isolated. Transcription factor p53 has been reported to mediate apoptosis by increasing the expression of cell surface Fas on human VSMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry fruit extract was also reported to protect pancreatic β cells against hydrogen peroxide‐induced oxidative stress and associated apoptotic cell death . Besides, a mulberry leaf diet was also reported to protect against the progression of experimental autoimmune myocarditis to dilated cardiomyopathy via modulation of oxidative stress and MAPK‐mediated apoptosis . However, the functional components that inhibited apoptosis in the above studies were not isolated.…”
Section: Introductionmentioning
confidence: 99%